Probing the emission dynamics in nitrogen-doped carbon dots by reversible capping with mercury(ii) through surface chemistry. (15th July 2022) - Roy, Dipayan; Das, Antika; Roy, Rajarshi; Das, Dimitra; Kumar Das, Bikram; Ghorai, Uttam Kumar; Chattopadhyay, Kalyan Kumar; Sarkar, Sourav
Abstract : Synopsis: PL emission centre determination of N-CQDs by a reversible quenching mechanism. Abstract : In this study, the mechanistic insight and emission dynamics have been explored for size-dependent nitrogen-doped carbon quantum dots (namely 3A, 3B & 3C) with toxic metal Hg 2+ ions via a capping and uncapping mechanism. The excitation and pH-dependent emission profile of N-CQDs is assigned to multiple centers involving higher energy aromatic core states (π–π*) and lower energy oxygen- and nitrogen-based functional groups (nO2 p–π* and nN2 p–π*). From experimental and theoretical validation, the highly negatively charged surface of 3A is found to be mainly due to the high abundance of –COOH and NH2 groups promoting weak (COO − )2 –Hg 2+, NH2 –Hg 2+ bond formation with the reduction of the sp 2 carbon content with different concentrations of Hg 2+ ions. Thus, the combined effect shrinks the P.L. signals (area and intensity) associated with the π–π* and n–π* transitions through the static and dynamic quenching pathway (LOD ∼ 0.209 μM). Furthermore, the restoration of PLE and P.L. signals is carried out by uncapping Hg 2+ ions. The high recovery percentage (∼maximum −96%) is mainly governed by COOH and NH2 groups rather than the deeply buried core state. Thus, the prominent reversible quenching associated with surface states is well supported by changes in zeta potential measurements. Our investigation demonstrates the direct dependence of surface chemistry on the proposed emission dynamics of carbon dots.